Vita activa e lex naturae in Cromazio di Aquileia: il caso di Sermo III - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Filosofía Alejandro Korn. Sección de Filosofía Medieval., 2021)
The Sermones of Chromatius of Aquileia offer us direct evidence of his episcopal and literary experience, divided between the most marked exegesis and the pastoral objective. The structural and linguistic simplicity and the reference to a few contemporary authors, characteristics of the third of these homiletic compositions, offer us the opportunity to analyse the most intimate and practical purposes of this text. The close relationship with the audience, in fact, and the intent to guide them on a right Christian path are evident protagonists in the flow of the entire sermon. At the same time, however, the scriptural exegesis of Chromatius and his doctrinal study run: the Bishop tries to offer a small baggage useful to the path of those who listen to him, in a strong enhancement of human action. The vita activa adhering to the lex naturae inherent in the human soul constitutes, in fact, the most evident theme of the entire homily, expounded by the Aquileian above all with the aim of strengthening the unity and the identity of the listeners in the face of external pressures. Above all, the scriptural reference is strong, present throughout the Sermo: the passage, certainly read just before the exposition, is almost entirely reported, and exposed to the faithful, so as to make it more fixed in the memory of those who attend.

Los Sermones de Cromacio de Aquilea nos ofrecen evidencia directa de su experiencia episcopal y literaria, que se divide entre la exégesis más destacada y el objetivo pastoral. La simplicidad estructural y lingüística, y la referencia a algunos autores contemporáneos, características de la tercera de estas composiciones homiléticas, nos ofrecen la oportunidad para analizar los propósitos más íntimos y prácticos de este texto. De hecho, la estrecha relación con su audiencia y el intento de guiarla por el justo camino cristiano son los evidentes protagonistas en todo el discurrir del sermón. Sin embargo, al mismo tiempo se observa también la exégesis escritural de Cromacio y su profundización doctrinal: el Obispo trata de ofrecer un pequeño pero útil bagaje para el camino de quien lo escucha, en una poderosa valorización de la acción humana. La vita activa que se suma a la lex naturae inherente al alma humana constituye, de hecho, el tema más evidente de la homilía íntegra, que expone el de Aquilea sobre todo con el objetivo de fortalecer la unidad y la identidad de quienes escuchan cuando enfrentan presiones externas. La referencia escritural es fuerte y está presente en todo el sermón: el pasaje, seguramente leído justo antes de la exposición, se expone casi en su totalidad a los fieles, para fijarlo mejor en la memoria de aquellos que asisten a la lectura.
Vita activa and lex naturae in Chromatius of Aquileia: the case of Sermo III
Fil: Conti, Federico. Universidad Pontificia Salesiana. Pontificium Institutum Altioris Latinitatis; Italia
Keywords: CHROMATIUS; SERMONES; ACTION; PELAGIANISM; IDENTITY; CROMACIO; SERMONES; ACCION; PELAGIANISMO; IDENTIDAD